Persistence of Varicella-Zoster Virus Cell-Mediated Immunity After the Administration of a Second Dose of Live Herpes Zoster Vaccine. (28th August 2018) - Weinberg, Adriana; Popmihajlov, Zoran; Schmader, Kenneth E; Johnson, Michael J; Caldas, Yupanqui; Salazar, Adriana Tovar; Canniff, Jennifer; McCarson, Barbara J; Martin, Jason; Pang, Lei; Levin, Myron J
Abstract : This study shows that older adults who received a second dose of ZVL ≥10 years after the first dose lose their VZV-specific T-cell responses over time and maintain only a marginally higher memory responses compared with de novo immunized controls. Abstract: Protection against zoster conferred by zoster vaccine live (ZVL; Zostavax) wanes over time. We compared varicella-zoster virus cell-mediated immunity (VZV-CMI) of adults ≥70 years who received a second dose of ZVL ≥10 years after the initial dose with de novo-immunized age-matched controls. Before and during the first year after vaccination, VZV-CMI was significantly higher in reimmunized compared with de novo vaccinees. At 3 years, VZV-CMI differences between groups decreased and only memory responses remained marginally higher in reimmunized participants. In conclusion, the increase in VZV-CMI generated by reimmunization with ZVL is at least equally persistent compared with de novo immunization.